Optimizing filter parameters using particle swarm optimization / Nik Ahmad Nizam Nik Zainuddin - Nik Zainuddin, Nik Ahmad Nizam (2009)
Filters of some sort are essential to the operation of most electronic circuits. It is therefore in the interest of anyone involved in electronic circuit design to have the ability to develop filter circuits capable of meeting a given set of specifications. Unfortunately, many in the electronics field are uncomfortable with the subject, whether due to a lack of familiarity with it, or a reluctance to grapple with the mathematics involved in a complex filter design. Filter designers often have to calculate the best parameters to suit the filter specifications. Software is typically used to help estimate those values, but sometimes the parameter combination cannot yield perfect results. Calculating the filter parameters using transfer functions would be more challenging with filters that have high orders. This project presents an application of a Particle Swarm Optimization algorithm (PSO) for designing high order filter. The proposed algorithm was successfully applied on a sixorder elliptic filter, and has been shown to work well. It is applied by calculating the mean-squared error between the ideal response and the actual response of the signal. Results have showed that the PSO have able to find all parameters with the least amount of mean-squared error.